Efectos sistémicos de los fangos minerales. Revisión de la literatura de los últimos 10 años - Michele, Daniel De (Anales de Hidrología Médica, 2007)
Objetives: mud systemic actions reported in last 10 years in medical literature are reviewed. Preponderance of European authors in literature, is remarkable. Almost there is no doubt about the nature of local mud effects on certain clinical settings, such as degenerative articular processes, skin disorders, and others. Thermal effect of the water bath is substantially smaller than that of the peat and mud applications, due to the high values of the dynamic viscosity. System action occur because of overlapping of several mechanisms; chemical mediators releasing, inflammation hormones, nitric oxide and serum levels of some amino acids modifications, beta-endorphin levels, some changes in performance of leukocytes and macrophages, drop of pro-inflammatory cytokines, and other. The microcirculatory changes mud-induced, in some instances, lasted longer than did the temperature increase. Thus, the biochemical action has aside from their physical-thermal effects. Several systemic effects of saline muds over human physiology and pathology, have been cleared in last 10 years.